Trademark Infringement: An Analysis of the Gudang Garam versus Gudang Baru Case and Its Global Implications: Pelanggaran Merek Dagang: Analisis Kasus Gudang Garam versus Gudang Baru dan Implikasi Globalnya - Goesman, Goesman; Markoni, Markoni (Rechtsidee, 2023)
This study conducts a qualitative analysis of the trademark dispute between Gudang Garam and Gudang Baru concerning brand names and imagery on products, employing a case study method alongside normative legal and conceptual approaches. The research delves into the judges' legal considerations and the trademark rights arrangement, focusing on Gudang Garam, a renowned brand. The results establish that Gudang Baru violated the 2016 trademark registration provisions (Article 1 Paragraph (1) of Law N 20 and Article 18 Paragraph (3) of Ministerial Regulation No. 67), prompting the Intellectual Property Office to reject all applications. This case underlines the importance of respecting well-established brands and legal implications for trademark registrations, informing future practices in the field.Highlights: Violation of trademark registration provisions by Gudang Baru. Enforcement of the trademark rights of well-known brand Gudang Garam. Legal implications influencing future trademark registration practices. Keywords: Trademark Dispute, Gudang Garam, Gudang Baru, Trademark Registration, Legal Implications.